2001
DOI: 10.1074/jbc.m108701200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Candida albicans Ferrichrome Transporter and Its Characterization by Expression inSaccharomyces cerevisiae

Abstract: Saccharomyces cerevisiae can accumulate iron through the uptake of siderophore-iron. Siderophore-iron uptake can occur through the reduction of the complex and the subsequent uptake of iron by the high affinity iron transporter Fet3p/Ftr1p. Alternatively, specific siderophore transporters can take up the siderophore-iron complex. The pathogenic fungus Candida albicans can also take up siderophore-iron. Here we identify a C. albicans siderophore transporter, CaArn1p, and characterize its activity. CaARN1 is tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 31 publications
4
61
0
Order By: Relevance
“…The copper dependence of elemental iron uptake contrasts with the copper independence of iron uptake from the siderophore ferrichrome. A single siderophore permease homologue is present in the genome of C. albicans that may mediate ferrichrome uptake (Lesuisse et al, 2001 ;Ardon et al, 2001), C. albicans may even synthesize its own siderophores (Ismail et al, 1985), providing even greater versatility in scavenging iron.…”
Section: Discussionmentioning
confidence: 99%
“…The copper dependence of elemental iron uptake contrasts with the copper independence of iron uptake from the siderophore ferrichrome. A single siderophore permease homologue is present in the genome of C. albicans that may mediate ferrichrome uptake (Lesuisse et al, 2001 ;Ardon et al, 2001), C. albicans may even synthesize its own siderophores (Ismail et al, 1985), providing even greater versatility in scavenging iron.…”
Section: Discussionmentioning
confidence: 99%
“…No vacuolar staining was seen in ⌬cwh36 cells with any of the antibodies. Assembly of the vacuolar H ϩ -ATPase is sequential, with the V 0 subunit being required for the addition of the V 1 subunit to the complex (15). Examination of VMA subunits in ⌬cwh36 cells by Western analysis revealed a marked reduction in the amount of Vph1p, but the V 1 subunits Vma1p and Vma2p were present (Fig.…”
Section: Fig 4 Iron Transport and Fet3p Immunofluorescence Studies mentioning
confidence: 98%
“…Genes encoding ferric reductases have been cloned from C. albicans (22), and there have been several reports on possible siderophore production by C. albicans (23)(24)(25). Either the siderophore-bound iron may be released by the ferric reductases and then picked up by the high-affinity uptake system (18, 26 -28), or the siderophoreiron complex is transported into the cell via receptor-mediated mechanisms (28,29). Thus, it is likely that the siderophoremediated iron binding may function upstream of and provide free iron to the oxidase-permease iron uptake system.…”
mentioning
confidence: 99%
“…These proteins belong to the major facilitator superfamily, whose members have been found in many organisms. Currently, one siderophore transporter gene (CaARN1) has been found in C. albicans, and its function has been investigated by heterologous expression in S. cerevisiae (28,29). Ardon et al (29) reported that CaArn1p expressed in S. cerevisiae specifically mediates the uptake of FC 1 -iron, but does not transport iron bound to FOB.…”
mentioning
confidence: 99%